Penerapan Data Mining Menggunakan K-Means Untuk Penentuan Penerima Bantuan Langsung Tunai (BLT) Dana Desa Pada Desa Cempaka Timur - Huswatun Hasanah; Pakarti Riswanto; Sidik Rahmatullah (Institut Bakti Nusantara, 2023)
Direct Cash Assistance is the provision of a sum of money to underprivileged people. This assistance is to help underprivileged communities in dealing with the corona virus (Covid19). In the distribution of Direct Cash Assistance, problems often occur as the distribution is not fully on target. BLT recipients were not on target because the determination process still used manual bookkeeping and the computerized process used MS. Excel so that the level of accuracy of data processing is still in doubt. Therefore to predict the determination of BLT recipients using the K-Means method and its implementation using MS. Excel and Python. Given that this method is one of those utilized to group data as a reference in making decisions on clustering sizable amounts of data, it is quite ideal for applying the predictions of BLT-DD Assistance recipients. From the results obtained in the processing of Direct Cash Assistance data using attributes that greatly influence, namely work, status of residence, income and number of dependents by obtaining two clusters, namely feasible or not feasible. In 2020 there were 38 eligible recipients of direct cash assistance and 72 inappropriate categories, in 2021 there were 30 eligible recipients of cash assistance and 70 inappropriate categories, in 2022 there were recipients of direct cash assistance with the category 29 people are eligible and 61 people are not eligible.